2008
DOI: 10.1093/aje/kwn185
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Disability and the Urban Built Environment

Abstract: Research on the effects of the built environment in the pathway from impairment to disability has been largely absent. Using data from the Chicago Community Adult Health Study (2001-2003), the authors examined the effect of built environment characteristics on mobility disability among adults aged 45 or more years (n = 1,195) according to their level of lower extremity physical impairment. Built environment characteristics were assessed by using systematic social observation to independently rate street and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
185
5
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(209 citation statements)
references
References 30 publications
10
185
5
9
Order By: Relevance
“…Several studies have documented associations between different health outcomes and neighborhood characteristics, after accounting for differences in individual-level characteristics across neighborhoods. Such associations have been reported for a diversity of health outcomes including cardiovascular diseases [7][8][9] , mortality 10,11 , mental health outcomes [12][13][14][15][16] , physical activity 17,18 , and perceived health 19 , among others [20][21][22] . Many studies have used census-based indicators, constructed by aggregating the socioeconomic characteristics of residents as proxies for the more specific neighborhood features hypothesized to be relevant to health.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have documented associations between different health outcomes and neighborhood characteristics, after accounting for differences in individual-level characteristics across neighborhoods. Such associations have been reported for a diversity of health outcomes including cardiovascular diseases [7][8][9] , mortality 10,11 , mental health outcomes [12][13][14][15][16] , physical activity 17,18 , and perceived health 19 , among others [20][21][22] . Many studies have used census-based indicators, constructed by aggregating the socioeconomic characteristics of residents as proxies for the more specific neighborhood features hypothesized to be relevant to health.…”
Section: Introductionmentioning
confidence: 97%
“…26,27 One study in the city of Chicago found that older adults with movement-related impairments had a fourfold higher odds of reporting severe difficulty walking when living in neighborhoods with streets in poor condition (e.g., cracks, broken curbs, potholes) compared to those living in neighborhoods with streets in good condition. 28 Another study of older adults living in the Houston area found that curb cuts and bus shelters were non-existent in the vast majority (75 %) of respondent neighborhoods and fewer than 10 % of respondents used public transportation even though close to half of these adults lived within two blocks of a bus stop. 16 Curb cuts, smooth pavement, and barrier-free sidewalks are just some of the many environmental factors that can enhance independence and social participation in older adults at greatest risk, such as those who are socially isolated, prone to falling, or those with underlying weakness in movement-related functions and balance.…”
Section: Introductionmentioning
confidence: 99%
“…Several of them also expressed their fear of falling when getting around, specifi cally because of a loss of balance, which occurs frequently in individuals with a TBI, regardless of age [19,37,38]. Insecurity and fear of suffering a fall are cause for concern for seniors with or without a TBI and are described as determining factors when choosing a neighborhood or a place to visit [5,7,[42][43][44][45][46][47]. Being able to move, getting out, and planning outings are essential to seniors since they promote improved cognitive and functional abilities, better quality of life, and physical health [7,8,48].…”
Section: Discussionmentioning
confidence: 99%